Peran Ekonomi Kreatif dalam Meningkatkan Industri Pariwisata di Seaworld Ancol - Dewi Retno Dumilah; Moh. Komarudin; Rian Ubaidillah; Sulastri Siagian; Sugeng Santoso (JURNAL MASTER PARIWISATA, 2021)
The tourism industry is an industry that can absorb many creative economic markets. The purpose of this paper is to evaluate the creative economic activities as added value that support the tourism industry. The creative economy analyzed here is the creative fashion economy, which is one of the supporters in providing direct income and advertising as a downstream chain of tourism to convey messages to consumers. Method used qualitative and quantitative by looking for regression between income and costs and based on questionnaires conducted on consumers. The results showed a relationship between costs of advertising incurred with income derived from visitor. In a qualitative analysis in the fashion subsector, fashion can contribute a value of 10-12% to revenue. To accelerate in this industry is by knowing the various sub-sectors that are part of the tourism industry value chain and increasing creativity and innovation of creative economic products (fashion and advertising). Keywords: creative economy; fashion; tourism industry, advertising; value chain.